1997
DOI: 10.1038/bjc.1997.375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toremifene and tamoxifen in post-menopausal patients with advanced breast cancer: a randomized double-blind, the 'nordic' phase III study

Abstract: SummaryThe study was planned to compare, in a prospective double-blind randomized trial, the efficacy and safety of toremifene (TOR) and tamoxifen (TAM) in post-menopausal patients with advanced breast cancer who have not had prior systemic therapy for advanced disease. Four hundred and fifteen post-menopausal patients with oestrogen receptor (ER)-positive or ER-unknown advanced breast cancer were randomly assigned to receive daily either 60 mg TOR or 40 mg TAM. The patients were stratified to measurable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…Fever and chills were significantly more common among tamoxifen-treated patients [35] . A safety analysis in the Finnish Breast Cancer Study Group data also illustrates the similar tolerability and safety profiles of toremifene; sweating and hot flashes being observed in more than half of the patients, followed by vaginal dryness and discharge with itching and depression observed in more than 20% of patients [32] . (Table 4) In no case were significant differences between toremifene and tamoxifen observed.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Fever and chills were significantly more common among tamoxifen-treated patients [35] . A safety analysis in the Finnish Breast Cancer Study Group data also illustrates the similar tolerability and safety profiles of toremifene; sweating and hot flashes being observed in more than half of the patients, followed by vaginal dryness and discharge with itching and depression observed in more than 20% of patients [32] . (Table 4) In no case were significant differences between toremifene and tamoxifen observed.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…A Nordic study compared toremifene 60 mg with tamoxifen 40 mg in 415 postmenopausal women with advanced breast cancer in a double-blind randomized manner [32] . Response rates were similar in toremifene and tamoxifen groups (31.5% vs 37.3%).…”
Section: Toremifene In Advanced Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As TOR is equally effective to TAM in breast cancer treatment, the approximately fivefold greater plasma exposure of TOR and NDM TOR relative to TAM and NDM TAM (resulting from the higher clinical dose at 60 mg for TOR vs. 20 mg for TAM) may offset the difference in the contribution of the active metabolites. [4][5][6][7] In conclusion, we found that CYP2D6 is not an essential enzyme in the metabolism and disposition of TOR or its primary metabolite NDM TOR. Although 4-OH TOR and 4-OH-NDM TOR were up to 360-fold more antiestrogenic than TOR and NDM TOR, the combined plasma concentrations of these highly potent and active 4-OH metabolites are likely clinically irrelevant.…”
mentioning
confidence: 93%
“…3 TOR is equally effective in breast cancer treatment. [4][5][6][7] However, TOR may have reduced genotoxicity and lower potential to induce secondary endometrial cancers 8,9 and may therefore be considered as an alternative to TAM as firstline therapy for patients with ER-positive advanced breast cancer.…”
mentioning
confidence: 99%